2021
DOI: 10.1027/0227-5910/a000688
|View full text |Cite
|
Sign up to set email alerts
|

Young People's Perspectives and Understanding of the Suicide Story in13 Reasons Why

Abstract: Abstract. Background: The Netflix drama 13 Reasons Why (13RW) focusing on the suicide of an adolescent girl became a global phenomenon. It was accompanied by intense public debate about the risks of exposing youth to fictional portrayals of adolescent suicide. Aims: To explore adolescents' subjective perspectives and understanding of 13RW focusing on the portrayal of adolescent suicide. Method: We applied a thematic analysis to qualitative data from interviews with 25 New Zealand adolescents eliciting views on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There has been concern that frequent social media use 20 and exposure to suicidal content in media can glorify and normalize suicide. 29 , 30 , 31 , 32 In addition, studies have shown that glorified and repeated exposure to suicide from the media can lead to suicide contagion. 33 The score found on the Glorification/Normalization subscale in this study further increases alarm over the acceptance and normalization of suicide among emerging adults.…”
Section: Discussionmentioning
confidence: 99%
“…There has been concern that frequent social media use 20 and exposure to suicidal content in media can glorify and normalize suicide. 29 , 30 , 31 , 32 In addition, studies have shown that glorified and repeated exposure to suicide from the media can lead to suicide contagion. 33 The score found on the Glorification/Normalization subscale in this study further increases alarm over the acceptance and normalization of suicide among emerging adults.…”
Section: Discussionmentioning
confidence: 99%